Changes in Health Care Use by Mexican American Medicare Beneficiaries Before and After a Diagnosis of Dementia - Downer, Brian (J Gerontol A Biol Sci Med Sci, 2020)
BACKGROUND: Evidence from predominantly non-Hispanic White cohorts indicates health care utilization increases before Alzheimer’s disease and related dementias (ADRD) is diagnosed. We investigated trends in health care utilization by Mexican American Medicare beneficiaries before and after an incident diagnosis of ADRD. METHODS: Data came from the Hispanic Established Populations for the Epidemiological Study of the Elderly that has been linked with Medicare claims files from 1999 to 2016 (n = 558 matched cases and controls). Piecewise regression and generalized linear mixed models were used to compare the quarterly trends in any (ie, one or more) hospitalizations, emergency room (ER) admissions, and physician visits for 1 year before and 1 year after ADRD diagnosis. RESULTS: The piecewise regression models showed that the per-quarter odds for any hospitalizations (odds ratio [OR] = 1.62, 95% CI = 1.43–1.84) and any ER admissions (OR = 1.40, 95% CI = 1.27–1.54) increased before ADRD was diagnosed. Compared to participants without ADRD, the percentage of participants with ADRD who experienced any hospitalizations (27.2% vs 14.0%) and any ER admissions (19.0% vs 11.7%) was significantly higher at 1 quarter and 3 quarters before ADRD diagnosis, respectively. The per-quarter odds for any hospitalizations (OR = 0.88, 95% CI = 0.80–0.97) and any ER admissions (OR = 0.89, 95% CI = 0.82–0.97) decreased after ADRD was diagnosed. Trends for any physician visits before or after ADRD diagnosis were not statistically significant. CONCLUSIONS: Older Mexican Americans show an increase in hospitalizations and ER admissions before ADRD is diagnosed, which is followed by a decrease after ADRD diagnosis. These findings support the importance of a timely diagnosis of ADRD for older Mexican Americans.